Sex segregation in the workplace : trends, explanations, remedies - Reskin, Barbara F. (National Academy Press, 1984)
How pervasive is sex segregation in the workplace? Does the concentration of women into a few professions reflect their personal preferences, the "tastes" of employers, or sex-role socialization? Will greater enforcement of federal antidiscrimination laws reduce segregation? What are the prospects for the decade ahead? These are among the important policy and research questions raised in this comprehensive volume, of interest to policymakers, researchers, personnel directors, union leaders--anyone concerned about the economic parity of women
Revised versions of papers originally presented at a workshop held in May, 1982.
Keywords: Sex discrimination in employment -- United States -- Congresses.; Sex discrimination against women -- United States -- Congresses.; Discrimination sexuelle dans l'emploi -- États-Unis -- Congrès.; Discrimination à l'égard des femmes -- États-Unis -- Congrès.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Sex discrimination against women; Sex discrimination in employment; United States; USA; Arbeitsplatz; Aufsatzsammlung; Geschlechterrolle; Rassenfrage; Vrouwenarbeid.; Vrouwendiscriminatie.; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings.; Actes de congrès.